Adrenal Myelolipoma: 369 Cases From a High-Volume Center - Lin, Lede; Gong, Lina; Cheng, Liang; Liu, Zhihong; Shen, Sikui; Zhu, Yuchun; Zhou, Liang (Frontiers in Cardiovascular Medicine, 2021)
Background. Adrenal myelolipoma (AML) is a non-functional benign neoplasm from adrenal cortex, composed of mature fat and hematopoietic tissue. Usually, patients have no symptoms. However, some present with hypertension and blood pressure normalizes after surgery, indicating some connections between AML and hypertension. Materials and Methods. This was a retrospective cohort study of 369 patients diagnosed with AML from September 2008 to December 2018 collected in Urology Department of West China Hospital, Chengdu, Sichuan, China. We collected clinical records of patients before surgery. Postoperative follow-up was also done for those with hypertension and whether patients needed to take anti-hypertensive drugs and postoperative blood pressure were recorded. We aim to explore the characteristics of both AML patients with hypertension and remission of hypertension in 1 year after surgery. Results. There were 369 AML patients included in the study, 156 males and 213 females, aged 49.86±11.61 years old. Among them, 121 (32.8%) patients presented with hypertension. BMI was significantly higher in hypertension group than that in non-hypertension group, even after adjusting other variables (26.26±3.43 vs 24.28±3.38 kg/m2, P＜0.001 for both univariate and multivariate analysis). Sixty patients were followed up for 1 to 9 years, with a median follow-up of 52 months. The duration of hypertension in the remission group was shorter than that in the non-remission group (P=0.020), and tumor lateralization was significantly different between two groups (P=0.005). Conclusion. Nearly one third of AML patients suffered from hypertension in our study and there existed some potential links between AML and hypertension. To be more specific, AML-related hypertension was more likely to result from obesity and renal compression by PRF than from endocrine disorders or blood vessels compression. AML patients with more than 3years of hypertension might have less possibility to recover.